Programma: 20 juni The Young Gods; 21 juni Mathilde Santing; 24 juni I Like It Like That; 28 juni Jerry Lee Lewis
Programma: 20 juni The Young Gods; 21 juni Mathilde Santing; 24 juni I Like It Like That; 28 juni Jerry Lee Lewis.